MENIMBANG SEMANGAT PANCASILA DALAM RANCANGAN UNDANG-UNDANG PENGHAPUSAN KEKERASAN SEKSUAL (RUU P-KS) - Agung Nurrahman (Jurnal Kebijakan Pemerintahan, 2019)
Considering Pancasila Spirits In The Design Of Law Elimination Of Sexual Violence (RUU P-KS). There Was ongoing debate about this RUU, either its positively contribute towards sexual protection for women or its just a hidden agenda of radical feminist to manifest their ideology in indonesia. The purpose of this study is to know and analyze the value of the Pancasila in the draft law on the elimination of sexual violence (P-KS bill) in indonesia. This research is a library research method by examining various sources such as books and journals, documents, and draft legislation in the form of printed and electronic reports. Based on the study and analysis that has been carried out, the content contained in the P-KS bill does not reflect the religious values that are upheld in the Pancasila as the ideology of the Indonesian Nation. Not only that, the tendency to strengthen is that the bill brings understanding and thinking that are contrary to the values of pancasila and religion. Keywords: design, law elimination, sexual violence, radical feminism, Pancasila